A Comparative Analysis of Individualism and Collectivism Effects on Customer Satisfaction in the Retail Sector: Examining Asian and Western Cultures - Abdul Halim, Abdul Hamid; Abdul Ghani, Wan Soraya Wan (Information Management and Business Review, 2023)
Customer satisfaction is the result of a customer’s assessment of how well a service has performed, stemming from the differences between their initial expectations and the actual service they have encountered. While various elements play a role in shaping customer satisfaction, numerous factors come into play. This study focuses on exploring cultural differences, considering the multicultural environment of Malaysia. This is particularly intriguing since businesses in Malaysia cater to both local and international customers from Asian and Western regions. The objective of this study is to examine the correlation between individualism and collectivism about customer service satisfaction, with a specific focus on the retail sector involving multinational brands and diverse customers. The utilization of Geert Hofstede’s Dimension theory is justified as it is a widely recognized framework for cultural differences research. A quantitative methodology was employed, surveying 103 participants, with 51.5% originating from Asian cultures and 48.5% from Western cultures. The findings demonstrate that while both individualism and collectivism significantly influence customer service satisfaction in the retail sector, collectivism plays a more significant role in determining overall satisfaction levels. To enhance the understanding of this topic, it is suggested that future studies expand beyond the Klang Valley area and explore additional explanatory variables that consider the impact of cultural differences on customer satisfaction.